Heat Evolution of Class C Fly Ash Geopolymers with Different Molarity of Sodium Hydroxide: Nucleation Growth and Morphology Properties towards Early Strength Evaluation. Issue 1 (May 2020) - Mohamed, Rosnita; Abd Razak, Rafiza; Mustafa Al Bakri Abdullah, Mohd; Khimi Shuib, Raa; Subaer,; Ahmad, Romisuhani; Hakem Aziz, Ikmal; Ahmad Sofri, Liyana
Abstract: The heat evolved during setting of class C fly ash geopolymers with different molarity of sodium hydroxide are discussed. The reaction kinetics and microstructure properties of geopolymers are studied towards the early strength development. Differential Scanning Calorimeter was applied to determine the heat evolved and Johnson-Mehl-Avrami-Kolmogrov Model was used to analyse the reaction kinetics during setting of the geopolymers. Morphology and strength development were monitored. The results revealed that the heat evolved increased proportionally with increasing molarity of sodium hydroxide. This indicated rapid reaction of geopolymerization due to the increasing of hydroxide ion content thus mainly affect dissolution process. It was also found that the geopolymerization during setting was governed by one-dimensional growth with instantaneous heterogeneous nucleation and this was supported by the morphology of the geopolymers observed. Among the activator molarities, the molarity of 12 (12M) was observed to be most influential based on its highest compressive strength (up to 46MPa at 7-days) and supported by the morphology properties results.